Analysis of the Magnitude of Load Shedding on Frequency Reduction at the UP3 Cotton Plantation Diesel Power Plant (PLTD) - Naomi Lembang (Universitas Khairun, 2024)
Load shedding due to frequency reduction in the Fakfak Regency electric power system occurred due to the overload of the KORMAN-01 engine with an installed power of 400 kW, operating power 200 kW, DOSSAN-02 engine, with installed power 500 Kw, operating power 500 kW, and KOMATSU-04 engine with installed power 800 Kw, operating power 600 at PLTD Kebun Kapas, PT. PLN (Persero) ULP FAKFAK, there was an overload on generating machines that were still operating due to a lack of power being generated where the power generated was less than the load on the system which decreased resulting in a black out. The aim is to determine the amount of load shedding when the frequency decreases by calculating. The results obtained by overloading the KORMAN-01, DOSSAN-02, KOMATSU-04 engines resulted in a decrease in frequency to 49,765 Hz, 48,883 Hz, 48,170 Hz approaching the normal frequency of 50 Hz and the calculated load shedding results were 198,108 kW, 23,092 kW, and 153,565 kW.